Identifying superior quality F1 tomato hybrids for year round production under low cost plastic greenhouses in North-West Himalayas - Sharma, Manish K; Kumar, Rajeev; Kumari, Santosh (Vegetable Science, 2011)
Tomato is an important crop of hilly regions in India and fetches off season prices to farmers when grown during rainy season in Himachal Pradesh. However, the production remains in scarcity during March-June and October- December due to environmental hazards. The only alternative is to make use of low cost plastic greenhouses for tomato production during these periods so that year round and off-season supply to the market in the plains is regulated. Keeping this in view, an experiment was conducted to evaluate and identify the superior and most promising F1 hybrids in respect of productivity and quality of the produce in a low cost plastic greenhouse. The study was carried out on 16 tomato hybrids in relation to earliness, yield and quality. Out of 16 hybrids, Naveen 2K+ recorded the maximum fruit yield/plant (3.23 and 3.81 kg) and fruit yield/m2 (12.92 and 15.24 kg) followed by Amisha and Rakshak. Naveen 2K+ also recorded maximum fruit weight (73.33 and 74.17 g), and harvest duration (73.33 and 74.67 days) during both the years. A cherry tomato hybrid BSS-366 was earliest in marketable maturity (78.67 and 79days) and recorded the maximum number of flowers/ cluster, number of fruits/ cluster, number of flower clusters/ plant, number of fruits/ plant, total soluble solids, ascorbic acid and lycopene content. Rakshak exhibited maximum value of pericarp thickness and shelf life.